Dr. Rolston receives Templeton Prize from Prince Philip - Shirley, Clifford, photographer (Colorado State University. Libraries, 2003)
Photograph featuring events during the May 7, 2003 Templeton Prize with H.R.H. Prince Philip, Duke of Edinburgh, at Buckingham Palace and others.
Keywords: Templeton laureates; Colorado State University; philosophy professor; Templeton Prize; Rolston, Holmes, 1932-2025